2006
DOI: 10.1158/0008-5472.can-06-0506
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glycosylphosphatidylinositol (GPI) Transamidase Subunits Phosphatidylinositol Glycan Class T and/or GPI Anchor Attachment 1 Induces Tumorigenesis and Contributes to Invasion in Human Breast Cancer

Abstract: Based on the oncogenic role of phosphatidylinositol glycan (PIG) class U in human tumors, we explored the role of two additional subunits of the glycosylphosphatidylinositol (GPI) transamidase complex in human breast cancer. We found that PIG class T (PIG-T) and GPI anchor attachment 1 (GPAA1) were overexpressed in breast cancer cell lines and primary tumors. Forced expression of PIG-T and GPAA1 transformed NIH3T3 cells in vitro and increased tumorigenicity and invasion of these cells in vivo. Suppression of P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 43 publications
3
71
0
Order By: Relevance
“…Of them, 42% showed amplification of PIG-U, 13% showed amplification of PIG-T and only 11.6% showed increased copy number of GPAA1. 9 Here, the fourth subunit, GPI8, showed higher accumulation in 64% of ovarian cancer and 67% of uterine cancer cases. The fifth subunit, PIG-S, did not show any significant deregulation in expression levels in breast, ovary or uterine cancers.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Of them, 42% showed amplification of PIG-U, 13% showed amplification of PIG-T and only 11.6% showed increased copy number of GPAA1. 9 Here, the fourth subunit, GPI8, showed higher accumulation in 64% of ovarian cancer and 67% of uterine cancer cases. The fifth subunit, PIG-S, did not show any significant deregulation in expression levels in breast, ovary or uterine cancers.…”
Section: Discussionmentioning
confidence: 82%
“…Wu et al 9 have recently reported on the amplification of three of the GPIT subunits in primary breast cancer cases. Of them, 42% showed amplification of PIG-U, 13% showed amplification of PIG-T and only 11.6% showed increased copy number of GPAA1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PIGU is overexpressed in bladder cancers and has been proposed as an oncogene in bladder (Guo et al 2004) and breast cancer (Wu et al 2006). PIGU protein has been found to be upregulated in prostate cancer (Nagpal et al 2008).…”
Section: Discovery Of Non-ets Gene Fusions In Prostate Cancermentioning
confidence: 99%